Teacher Competence and Attitudes as Determinants of National Plus Curriculum Implementation Effectiveness - Bunga Mega; Ronald Suryaputra; Dany Moenindyah Handarini (Journal of Educational Management Research, 2026)
This study aims to analyze the influence of pedagogical competence, professional competence, and teacher attitudes on the effectiveness of National Plus Curriculum implementation. A quantitative explanatory approach was employed, with data collected through a census survey involving teachers. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to examine both partial and simultaneous relationships among variables. The results show that pedagogical competence, professional competence, and teacher attitudes each have a positive and statistically significant effect on the effectiveness of curriculum implementation. Simultaneously, these variables demonstrate a strong combined influence on implementation effectiveness. Among the three factors, teacher attitude exhibits the largest effect size, indicating that motivation, commitment, and openness to curriculum change play a dominant role in supporting effective implementation. These findings imply that successful implementation of the National Plus Curriculum depends not only on teachers’ instructional skills and professional expertise but also on the development of positive attitudes toward curriculum change. Therefore, professional development programs should integrate competence enhancement with strategies aimed at strengthening teachers’ motivation and readiness for curricular innovation.